Nymphal description of Tricorythodes zagaia n. comb. and Tricorythodes pemonensis n. comb. (Ephemeroptera: Leptohyphidae) and first records from Colombia - Molineri, Carlos; Dias, Lucimar Gomes; Gonzalez, Ivan; Núñez-Avellaneda, Marcela (Zootaxa, 2019)
The nymphal stages of Tricorythodes pemonensis n. comb. and T. zagaia n.comb. are firstly described. The nymphal characters as well as the characteristic swelling at the base of second forceps segment in male imago justify moving them from Macunahyphes to Tricorythodes. Additionally, other three species described in Macunahyphes are also transferred to Tricorythodes: Tricorythodes araca (Souto & Salles) new comb., Tricorythodes eduardoi (Almeida & Mariano) new comb., and Tricorythodes incognitus (Molineri et al.) new comb. Macunahyphes australis is the only species that remains in the genus.